2020
DOI: 10.1136/bmjopen-2019-035004
|View full text |Cite
|
Sign up to set email alerts
|

Using trigger tools to identify triage errors by ambulance dispatch nurses in Sweden: an observational study

Abstract: ObjectivesThis study aimed to assess whether trigger tools were useful identifying triage errors among patients referred to non-emergency care by emergency medical dispatch nurses, and to describe the characteristics of these patients.DesignAn observational study of patients referred by dispatch nurses to non-emergency care.SettingDispatch centres in two Swedish regions.ParticipantsA total of 1089 adult patients directed to non-emergency care by dispatch nurses between October 2016 and February 2017. 53% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The inclusion criteria for this study select for patients cared for through the typical prehospital care pathway of ambulance transport to the ED, and many patients referred to alternate forms of care by dispatchers and ambulance crews, as is common in the studied region [ 20 ], were not included owing to the lack of relevant outcome data for these patients. It may also be that some cases of Covid-19 were hospital-acquired, and that prehospital care providers could not have been expected to identify them.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria for this study select for patients cared for through the typical prehospital care pathway of ambulance transport to the ED, and many patients referred to alternate forms of care by dispatchers and ambulance crews, as is common in the studied region [ 20 ], were not included owing to the lack of relevant outcome data for these patients. It may also be that some cases of Covid-19 were hospital-acquired, and that prehospital care providers could not have been expected to identify them.…”
Section: Discussionmentioning
confidence: 99%
“…This willingness to deviate from the CDSS indicates that RNs used their professional competence and autonomy, instead of being steered by the CDSS. While professional autonomy is desirable, previous studies have showed that triage errors in the context of EMDCs could have been avoided by greater compliance with CDSS (Andersen et al., 2014; Spangler et al., 2020). As such, optimal methods to gain the benefits of both professional autonomy and CDSS compliance should be identified through further research.…”
Section: Discussionmentioning
confidence: 99%
“…While CDSSs are intended to improve decision accuracy and patient safety, the professional autonomy of RNs could be limited by working through a rigid, mechanistic system. This tension could lead to RNs overruling the CDSS or using it only partially, which in turn might hamper patient safety (Spangler et al., 2020). Hence, more knowledge is needed of RNs views in these matters to enhance both technical development of CDSS and the work situation of RNs at EMDCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incident reporting system does not reflect the actual hospital-wide events in our centre, it is a worthwhile source of information from which to discover potential risks and attributable factors of a representative patient safety issue [3,9]. In this system, events whose potential consequences are difficult to measure in patient prognosis and which have been caused by external events or inappropriate or defective internal processes, systems, and/or systemic improvement activity are also indicated as risks [10]. Accumulation of near-miss incidents of the same type and with a small impact as a one-off event also carries the risk of potential adverse events.…”
Section: Resultsmentioning
confidence: 99%